PENGARUH PERBANDINGAN TERONG BELANDA (SOLANUM BETACEUM CAV.) DENGAN RUMPUT LAUT (EUCHEUMA COTTONII) TERHADAP KARAKTERISITIK LEATHER - Yuni Wulan Sari, Ni Putu; Mayun Permana, I Dewa Gede; Sugitha, I Made (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 7 No 2 (2018): Jurnal ITEPADO - 10.24843/itepa.2018.v07.i02.p07, 2018)
This study aimed to determine the effect of tamarillo and seaweed ratio on the characteristics of tamarillo leather and to know the optimum ratio of tamarillo and seaweed on the characteristics of leather. The experimental design was used completely randomized design with the ratio of tamarillo and seaweed as treatment, which consist of 6 levels such as: 100% : 0%, 95% : 5%, 90% : 10%, 85% : 15% : 80% : 20%, and 75% : 25%. The treatment was repeated as many as 3 times then obtained 18 units of the experiment, the data obtained from the result research were analyzed by variance and if the treatment had an effect on the variable then continued with Duncan test. The results showed that tamarillo and seaweed ratio had a significant effect on moisture content, total sugars, vitamin C, curde fiber content, color (score), texture and taste level (hedonic and score), and overall acceptance (hedonic) of leather. Ratio 75% : 25% is produce best characteristic with 12.61% moisture content, 23.93% total sugars, 33.70 mg/100g vitamin C, 21.81% curde fiber content, color rather orange and liked, typical aroma of tamarillo and liked, very elastic texture and very liked, typical of tamarillo taste and very liked, and overall acceptance of very liked.